Recycling of Waste Bamboo Biomass and Papermaking Waste Liquid to Synthesize Sodium Lignosulfonate/Chitosan Glue-Free Biocomposite - Qingzhi Ma; Guiyang Zheng; Jinxuan Jiang; Wei Fan; Shengbo Ge (Molecules, 2023)
The development of the paper industry has led to the discharge of a large amount of papermaking waste liquid containing lignosulfonate. These lignin black liquids cause a lot of pollution in nature, which runs counter to the current environmental protection strategy under the global goal. Through the development and use of lignosulfonate in papermaking waste liquid to increase the utilization of harmful substances in waste liquid, we aim to promote waste liquid treatment and reduce environmental pollution. This paper proposes a new strategy to synthesize novel glue-free biocomposites with high-performance interfacial compatibility from papermaking by-product sodium lignosulfonate/chitosan (L/C) and waste bamboo. This L/C bamboo biocomposite material has good mechanical properties and durability, low formaldehyde emissions, a high recovery rate, meets the requirements of wood-based panels, and reduces environmental pollution. This method is low in cost, has the potential for large-scale production, and can effectively reduce the environmental pollution of the paper industry, promoting the recycling of biomass and helping the future manufacture of glue-free panels, which can be widely used in the preparation of bookcase, furniture, floor and so on.